Sequestering a River: The Political Ecology of the "Dead" Ergene River and Neoliberal Urbanization in Today's Turkey - Acara, Eda (Annals of the American Association of Geographers, 2019)
This article explores the neoliberal authoritarian transformation of Turkey's water sector since 2000 by examining the policies surrounding the Ergene River, a dead river that runs through Turkey's European province of Thrace. Within the context of the accelerating neoliberalization of water resources in Thrace for the benefit of the Istanbul region at the expense of severe environmental pollution, the result was a combination of authoritarian policy prerogatives and priorities that rest on organized irresponsibility and a politics of nongovernance regarding environmental protection. As this article demonstrates, contemporary authoritarian neoliberalism in Turkey has created gray zones of authority involving many public authorities with varying and sometimes overlapping mandates, within which blatant breaches of the law became akin to the metropolitan municipal governance of distant water resources. Key Words: Ergene River, metropolitan municipality regimes, neoliberal urbanization, river pollution, Thrace region, Turkey. 本文通过检视围绕着额尔古纳河这条流经土耳其位于欧洲的色雷斯州的死河之政策, 探讨土耳其水资源部门自2000年以来的新自由主义威权转变。在加速色雷斯的水资源新自由主义化以嘉惠伊斯坦堡区域、并以严重的环境污染为代价的脉络中, 该结果是以组织化的不负责任为基础的威权政策特权与优先权和有关环境保护的非治理政治之组合。如同本文所证实, 土耳其当代的威权新自由主义, 已创造出涉及诸多公共职权的灰色权力地带, 并有着各种且有时相互重叠的命令, 其中公然违反法律, 近乎成为大都会市政府有关远距水资源的治理。 关键词: 额尔古纳河, 大都会市政体制, 新自由主义城市化, 河流污染, 色雷斯区域, 土耳其。 Este artículo explora la transformación autoritaria neoliberal del sector del agua de Turquía a partir del 2000 examinando las políticas relacionadas con el Río Ergene, una corriente muerta que fluye a través de la provincia europea de Tracia, en Turquía. En el contexto de una acelerada neoliberalización de los recursos hídricos de Tracia para beneficio de la región de Estambul, a expensas de severa contaminación ambiental, el resultado fue una combinación de prerrogativas políticas autoritarias y prioridades que descansan sobre la irresponsabilidad organizada y una política de desgobierno en lo que concierne a la protección ambiental. Como se demuestra en este artículo, el neoliberalismo autoritario contemporáneo en Turquía ha creado zonas grises de autoridad que involucran a muchas autoridades públicas, con mandatos variados y a veces traslapados, dentro de los cuales las descaradas burlas a la ley se asemejan a la gobernanza municipal metropolitana aplicada a los distantes recursos del agua.